Robust Properties of Membrane-Embedded Connector Channel of Bacterial Virus Phi29 DNA Packaging Motor - Jing, Peng (2010)
Biological systems contain highly-ordered macromolecular structures with diverse functions, inspiring their utilization in nanotechnology. A motor allows linear dsDNA viruses to package their genome into a preformed procapsid. The central component of the motor is the portal connector that acts as a pathway for the translocation of dsDNA. The elegant design of the connector and its channel motivates its application as an artificial nanopore. Herein, we demonstrate the robust characteristics of the connector of the bacteriophage phi29 DNA packaging motor by single pore electrophysiological assays. The conductance of each pore is almost identical and is perfectly linear with respect to the applied voltage. Numerous transient current blockade events induced by dsDNA are consistent with the dimensions of the channel and dsDNA. Furthermore, the connector channel is stable under a wide range of experimental conditions including high salt and pH 2–12. The robust properties of the connector nanopore made it possible to develop a simple reproducible approach for pore quantifications. Such quantifications led to a reliable real time counting of DNA passing through the channel. The fingerprint of DNA translocation in this system has provided a new tool for future biophysical and physicochemical characterizations of DNA transportation, motion, and packaging.